Penetrating facial injuries may cause intracranial damage - Maximillian Christian Oley; Mendy Hatibie Oley; Adrian Noldy Tangkilisan; Nidia Limarga; Muhammad Faruk (Elsevier, 2021)
Background: Due to the various injuries that can occur during the removal of odd objects, a penetrating facial trauma injury can cause a wide range of injuries. To avoid ophthalmic and/or neurological abnormalities in addition to the risk of infection and or bleeding, accurate diagnosis and prompt treatment are critical. An optimal treatment outcome is achieved through a thorough examination, radiological evaluation, and prompt decision-making. Case presentation: We report two cases of penetrating facial trauma injury caused by metal objects. Immediate medical examination and multidisciplinary intervention are critical for enhancing prognosis, ensuring a successful neurological recovery, and avoiding delayed consequences. At admission and before and after surgery, our client revealed no neurological deficits. Conclusions: Because of the potential for ocular and cerebral damage, penetrating fascial trauma injuries from metal items must not be overlooked. As a result, the purpose of this paper is to raise awareness of the complexity and severity of intracranial damage in addition to infection-related consequences caused by these types of injuries.